Acculturation, Mental Health, and Well Being: The Experience of Indonesian Students in Germany - Yuniarti, Kwartarini W. (ANIMA Indonesian Psychological Journal, 2009)
Being sojourners in Germany may cause Indonesian students stress due to acculturation. Acculturation in this study defined as culture change resulted from contact between two cultural groups. This study was to identify symptoms of general mental health status related to acculturation. The acculturation orientation and the general mental health status were measured using standardized psychometric instruments.Hypotheses were developed to see if there were any significant different on general mental health status of the students with regard to acculturation, length of stay and presence of families in Germany. A survey of 201 Indonesian students in Germany was conducted. Results were then compared to Indonesian students in Indonesia. It shows that more than a half of the sojourners kept their Asian values and behaviors. Significant different was observed on some aspects of psychological well- being, partly moderated by length of sojourning. “Hostility” was maximal in the first 2 months of sojourning and declining thereafter. Menjadi sojourner di Jerman bagi mahasiswa Indonesia barangkali dapat menyebabkan stress terkait dengan akulturasinya. Akulturasi didefinisikan sebagai interaksi dua kultur yang berbeda yang dialami pada waktu yang sama dan terus-menerus. Studi ini bertujuan untuk mengidentifikasi symptom kesehatan mental terkait dengan akulturasinya. Orientasi akulturasi dan kondisi mental mahasiswa diukur dengan instrument psikometris yang standard. Hipotesa: apakah ada perbedaan kesehatan mental secara umum pada mahasiswa Indonesia di Jerman terkait dengan orientasi culturalnya, lama tinggal, serta keberadaan keluarga di Jerman. Survei terhadap 201 mahasiswa Indonesia di Jerman dilakukan secara “cross-sectional”. Hasilnya dibandingkan dengan mahasiswa Indonesia di Indonesia dengan kelompok yang sama. Hasil menunjukan bahwa lebih dari 50% mahasiswa Indonesia di Jerman tetap berorientasi pada nilai-nilai dan perilaku Asia terlepas dari lama tinggal di Jerman. Perbedaan signifikan ditemukan pada beberapa aspek kesehatan mental terkait dengan lama tinggal di Jerman. “Hostility” paling tinggi dialami oleh mahasiswa untuk 2 bulan pertama di Jerman.